INFLUENCE OF VACUUM EVAPORATION PROCESS ON THE INDEX QUALITY OF YARNS - Xaydarov , Ulug‘bek Panjievich; Tulanov , Shamsiddin Erkayevich; Rixsiboyev , Ibrohim Rustam o‘g‘li (Innovative Development in Educational Activities, 2023)
In this article, samples were taken at a joint venture of the German firm Tryuchler, located in Tashkent, and some of them were vacuum evaporated and vacuum evaporated. The quality characteristics of the 24-tex yarn made from a mixture of 100% cotton and 30% polyester fiber with 70% cotton fiber were compared with the results of vacuum-stranded yarn testing.